2017
DOI: 10.1242/jcs.200139
|View full text |Cite|
|
Sign up to set email alerts
|

ICAP-1 monoubiquitylation coordinates matrix density and rigidity sensing for cell migration through ROCK2–MRCKα balance

Abstract: There was an error published in J. Cell Sci. 130, 626-636.The name of the author Alexander Kyumurkov was incorrect in the original author list. The correct spelling is given above.The authors apologise to the readers for any confusion that this error might have caused. 1195 ABSTRACTCell migration is a complex process requiring density and rigidity sensing of the microenvironment to adapt cell migratory speed through focal adhesion and actin cytoskeleton regulation. ICAP-1 (also known as ITGB1BP1), a β1 integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
1
8
0
1
Order By: Relevance
“…Previously known as a regulator of cell migration, 33,34 and cell‐shape related cytoskeletal reorganization 35 (such as polarization, 36,37 protrusion, 38,39 and extrusion 40 ) in neurons, epithelial cells and osteoblasts, we show here the presence of MRCKα in the EPOR‐TFR2 complex in erythroblasts, and that MRCKα is required for efficient erythropoiesis. However, the mechanism by which MRCKα regulates erythropoiesis remains elusive.…”
Section: Discussionsupporting
confidence: 58%
“…Previously known as a regulator of cell migration, 33,34 and cell‐shape related cytoskeletal reorganization 35 (such as polarization, 36,37 protrusion, 38,39 and extrusion 40 ) in neurons, epithelial cells and osteoblasts, we show here the presence of MRCKα in the EPOR‐TFR2 complex in erythroblasts, and that MRCKα is required for efficient erythropoiesis. However, the mechanism by which MRCKα regulates erythropoiesis remains elusive.…”
Section: Discussionsupporting
confidence: 58%
“…Our present results implicate a critical contribution of the integrin inhibitor, ICAP-1, in cellular mechanotransduction by working in concert with NME2 NDPK to control clathrin-mediated endocytosis of integrins at the edge of FAs. This new mechanism illustrates the importance of integrin inhibitors in mechanosensing and mechanoresponsiveness (Bouin et al, 2017;Lerche et al, 2020). Mechanistically, ICAP-1 acts as an adaptor protein in integrin endocytosis.…”
Section: Discussionmentioning
confidence: 74%
“…S1, D and E ), we checked that the combined deletion of β1 integrin and ICAP-1 did not affect the total expression of β3 integrin. Cells were seeded on Fn-coated polyacrylamide hydrogels (PA hydro gels) with a Young’s modulus (E) of 5 kPa as previously described ( Bouin et al, 2017 ). First, we observed that osteoblasts lacking β1 integrin ( β1 integrin –/– -icap-1 +/+ ) were defective in force generation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, their in vitro data might point towards a certain resistance to ROCK inhibition in EWS cells. Of note, it is well established that >1 µM SR3677 acts on several off-target kinases ( 33 ) including PKA [which promotes tumor growth and metastasis in EWS ( 37 ), MRCK [another mediator of cell contractibility ( 38 ) and AKT1 that plays important roles in EWS survival ( 39 ).…”
Section: Discussionmentioning
confidence: 99%